Outer-shell photodetachment of the metastable Be- 1s22s2p2 4Pe state (2003)
ABSTRACT: We report calculated photodetachment cross sections from the metastable Be- 1s22s2p2 4Pe state in the photon energy range 0–10 eV. Outer-shell photodetachment takes place in this energy range, which includes the double-ionization threshold Be+(2Se) at ~7 eV as well as doubly excited thresholds of the residual atom up to the Be(1s22p4 f ) threshold at ~10 eV. Therefore, triply excited states of Be- are reached within the selected photon energy. We have implemented the complex scaled configuration interaction method along with a model potential for the 1s2 core to uncover the first series of Be- 4Lo resonant states. In this work, four 4Po, seven 4Do, and two 4So resonances are reported and we compare our cross section with other previous theoretical calculations, that reported none or, at most, two resonances.